Lactate is always the end product of glycolysis - Rogatzki, Matthew J.; Ferguson, Brian S.; Goodwin, Matthew L.; Gladden, L. Bruce (Frontiers in Neuroscience, 2015)
Through much of the history of metabolism, lactate (La-) has been considered merely a deadend waste product during periods of dysoxia. Congruently, the end product of glycolysis has been viewed dichotomously: pyruvate in the presence of adequate oxygenation, La- in the absence of adequate oxygenation. In contrast, given the near-equilibrium nature of the lactate dehydrogenase (LDH) reaction and that LDH has a much higher activity than the putative regulatory enzymes of the glycolytic and oxidative pathways, we contend that La- is always the end product of glycolysis. Cellular La- accumulation, as opposed to flux, is dependent on 1) the rate of glycolysis, 2) oxidative enzyme activity, 3) cellular O2 level, and 4) the net rate of La- transport into (influx) or out of (efflux) the cell. For intracellular metabolism, we reintroduce the Cytosol-to-Mitochondria Lactate Shuttle. Our proposition, analogous to the phosphocreatine shuttle, purports that pyruvate, NAD+, NADH, and La- are held uniformly near equilibrium throughout the cell cytosol due to the high activity of LDH. La- is always the end product of glycolysis and represents the primary diffusing species capable of spatially linking glycolysis to oxidative phosphorylation.